2014
DOI: 10.1038/srep05615
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and phosphorus addition impact soil N2O emission in a secondary tropical forest of South China

Abstract: Nutrient availability greatly regulates ecosystem processes and functions of tropical forests. However, few studies have explored impacts of N addition (aN), P addition (aP) and N×P interaction on tropical forests N2O fluxes. We established an N and P addition experiment in a tropical forest to test whether: (1) N addition would increase N2O emission and nitrification, and (2) P addition would increase N2O emission and N transformations. Nitrogen and P addition had no effect on N mineralization and nitrificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 57 publications
(97 reference statements)
5
52
1
Order By: Relevance
“…In addition, the N 2 O-N:N 2 -N ratio was an order of magnitude higher (range 0.01-0.03) than any other groundwater sampled. These results support many previous studies that have shown high concentrations of NO 3 -contribute to higher concentrations of N 2 O (Weier et al 1993;Skiba et al 1998;Wang et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the N 2 O-N:N 2 -N ratio was an order of magnitude higher (range 0.01-0.03) than any other groundwater sampled. These results support many previous studies that have shown high concentrations of NO 3 -contribute to higher concentrations of N 2 O (Weier et al 1993;Skiba et al 1998;Wang et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Different letters above bars indicate significant differences among the P addition and N addition treatments (P < 0.05, Tukey's HSD test). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 limited by P. Phosphorus addition increased nitrification, denitrification and gaseous N emissions in upland (Mori et al, 2010;Fisk et al, 2014;Wang et al, 2014;Zhang et al, 2014) and wetland soils (White and Reddy, 2003). Microbes in general have a high P requirement, mostly for synthesis of RNA that can contribute 70e90% of total microbial P, which increases with increased microbial activity (Makino and Cotner, 2004;Franklin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A fertilization study in a TDF in India showed that N pools and mineralization rates increased with added N (Verma et al, 2013); however, both nitrogen cycling (Saynes et al, 2005) and nutrient addition effects on N cycling in another TDF in Mexico depended on season and forest successional status (Solís and Campo, 2004). Last, nitric and nitrous oxide emissions should increase under N deposition, particularly during the wet season (Erickson et al, 2002;Wang et al, 2014), and especially from N-saturated or P-limited forests (Hall and Matson, 1999).…”
Section: Ecosystem Processes: Soil Carbon Dynamicsmentioning
confidence: 99%